F&E Food Delivery / Nur Hanis Amirah Ahmad Zamri ... [et al.] - Ahmad Zamri, Nur Hanis Amirah; Khan, Syed Muhammad Adli; Ahmad Mustapha, Azman Ariff; Abd Razak, Muhammad Muizzudin (2021)
F&E FOOD DELIVERY is a newly operated business in Petaling Jaya. The name F&E represent "Fast and Efficient” which is also our company’s motto. Align with our motto, we want our customers to get their order fast by offering a quality rider who do their job efficiently. We provide training session to our rider and prepared them to be reliable and efficient. F&E offer a food delivery service to the community during this pandemic to make it accessible and convenient to our consumers. Our company focus on quality and our service is the cheapest among competitors. We only charge RM12 to our partners which is business owners from many restaurants. Not just that, our partners will get benefit from this because they will earn more compared to what they sell offline. With this, our service not only benefit us, but the customers, the public, and the business owners. Also, our location is very strategic because it is located near big malls, shops lot, residential area and campuses. The location is present with our target market which is individuals aged 15-54 years old. Our company runs by 4 manager which general manager, marketing manager, operation manager and financial manager. Not to forget our company also hired a clerk to do general works. Finally, we feel that our business financial statement will enable us to fulfill our business aim. We are confident that the positive people perception of our service will expand because of our company's great performances, which focus on precision and quality.